Resepsi siswa sekolah dasar terhadap syair lagu Indonesia Raya 3 stanza - Gandeswari, Theresia Luis; Wahyuningsih, Siti; Karsono, Karsono (Didaktika Dwija Indria, 2022)
The purpose of this study is to identify the level of reception of the Indonesia Raya 3 Stanza song lyrics by SD Negeri Bumi I Surakarta students in the 2021/2022 academic year. This study is also to describe the reception of the meaning of the Indonesia Raya 3 Stanza lyrics by SD Negeri Bumi I Surakarta students in the year 2021/2022. This research is qualitative research with a case study approach. The research subjects are students in 4th and 5th  grades of SD Negeri Bumi 1 Surakarta. The amount of this study’s research subjects are 35 students. Sources of data come from teachers and students. Data collection techniques: observation, interviews, and documentation or archives. The validity of the data using the technique of triangulation techniques. Data analysis used comparative descriptive statistical analysis techniques and critical analysis. Based on the results, it can be described that: (1) All of 4th and 5th graders student on SD Negeri Bumi I Surakarta don’t memorize the lyrics of Indonesia Raya 3 Stanza anthem; (2) Most of the 4th and 5th graders student on SD Negeri Bumi I Surakarta don't memorize the lyrics to the Indonesia Raya Stanza I anthem; (3) The reception of Indonesia Raya Stanza 3 anthem on 4th and 5th graders student on SD Negeri Bumi I Surakarta is positive.